Co-Chemotherapeutic Effect of n-Hexane Fraction of Binahong (Anredera cordifolia [Tenore] Steen.) on WiDr Colon Cancer Cell Line - Febriansah, Rifki; Lakshita, Harena Anggun (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: The incidence of colon cancer ranks the third most common cancer case in Indonesia, with 12.8 cases per 100.000 community. Problems that arise from cancer treatment with chemotherapy are severe side effects. Thus, we develop cancer therapy using a natural material, namely, binahong leaves (Anredera cordifolia). AIM: This study aims to investigate the co-chemotherapy activity of the n-hexane fraction of binahong (NFB) on the WiDr human colon cancer cells line. METHODS: The sample was prepared by maceration using ethanol 70% and fractionation using n-hexane. Phytochemical screening was conducted with the thin-layer chromatography method. The antioxidant test was carried out using 1,1 diphenyl-2-dipicrilhydrazil assay, while the 3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide assay was designed for cytotoxic tests on WiDr colon cancer cells to identify the single effect and its combination with 5-fluorouracil as chemotherapy agents. Further, in silico test, molecular docking was used to determine the 4’, 6, 7-trihydroxyaurone as an active compound on NFB against inhibitors of κB kinases (IKK) and COX-2 proteins. RESULTS: Phytochemical screening showed that NFB contained a flavonoid compound. NFB had a weak antioxidant activity with the inhibition concentration (IC50) value of 2851 μg/mL, while NFB had a relatively strong cytotoxic activity on WiDr colon cells with the IC50 value of 191 μg/mL, and had the synergist activity in combination with 5-fluorouracil as a chemotherapy agent. The molecular docking showed the best interaction of 4’, 6, 7-trihydroxyaurone against IKK, and COX-2 proteins with docking scores of −9.0 kcal/mol and −8.1 kcal/mol, respectively. CONCLUSION: NFB had the potential to inhibit cell growth and had a synergistic effect in combination with 5-fluorouracil on WiDr colon cancer cells line.